Perpaduan Kebudayaan Hindu – Islam dalam Babad Pura Langgar di Desa Bunutin, Kabupaten Bangli, Bali - Pande Wayan Renawati (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2014)
AbstrakSetiap umat di dunia ini seyogyanya hidup saling memahami, menghargai, dan saling membantu satu sama lain, karena hidup manusia di dunia akan saling membutuhkan. Untuk itu diperlukan adanya kehidupan yang romantis dan harmonis yang didasarkan oleh hati yang tulus dan suci, guna mewujudkan perdamaian yang berkesinambungan. Sehingga mampu mewujudkan kebahagiaan yang bisa diwariskan oleh anak cucu di masa yang akan datang. Sehubungan dengan keharmonisan tersebut, di Bali ada sebuah pura yang terkenal dengan terdapatnya dua jenis bangunan suci baik Hindu maupun Islam dalam satu wilayah pura, namanya Pura Langgar yang letaknya di Desa Bunutin Kabupaten Bangli. Hal ini telah menjadi tempat untuk bersembahyang bagi kedua umat baik Hindu maupun Islam sejak dahulu hingga sekarang, yang menunjukkan sebagai bukti keharmonisan Hindu dan Islam yang telah terjalin sejak masa lalu. Pura ini menjadi tempat pertemuan dua kebudayaan yang berbeda baik Hindu dan Islam sehingga kerukunan yang ada hingga sekarang bermula dari pura ini. Terkait dengan hal itu sangat menarik untuk dipahami sejarah maupun keunikan Pura Langgar tersebut.—AbstractBali is famous for its inherent culture in the form of religious art and culture which attracted foreign and domestic tourists visiting to see from close range on the art form of carving, sculpture, dance, and other traditions that inherited from the ancestors in the past. Similarly, the ornament is on houses and sacred buildings that are always innovating along with the times.The population is predominantly Hindu with a festive ceremony that almost done everyday making all creatures feel happy and have been satisfied at home, shrine or temple. Certainly, the ceremony was based on the awareness that every nation in the world should understand, respect, and help each other, recognizing the existence mutual need, mutual dependency and complementary in order to inter-religious harmony and understanding the importance of a large family and friendship intact. It required a romantic life and harmony based on the true heart and pure, in order to achieve sustainable peace. So as to realize the happiness that can be inherited by our children and grandchildren in the future. Regarding such Balinese harmony, there is a famous temple with the presence of two types of sacred building both Hinduism and Islam in the area of the temple, Pura Langgar that is located in the village of Bangli Regency Bunutin. It has become a place to pray for the people of both Hindu and Muslim since along ago. It shows as evidence that Hindu and Islamic harmony that has existed since the past.This temple is a meeting place of two different cultures both Hinduism and Islam so that harmony which exists today originated from this temple. It is very interesting to understand the history and uniqueness of the Pura Langgar.